Impact of adverse environmental conditions on rotorcraft operational performance and pollutant emissions - Ortiz-Carretero, Jesus; Castillo Pardo, Alejandro; Goulos, Ioannis; Pachidis, Vassilios (ASME, 2017)
It is anticipated that the contribution of rotorcraft activities to the environmental impact of civil aviation will increase in the future. Due to their versatility and robustness, helicopters are often operated in harsh environments with extreme ambient conditions. These severe conditions not only affect the performance of the engine but also affect the aerodynamics of the rotorcraft. This impact is reflected in the fuel burn and pollutants emitted by the rotorcraft during a mission. The aim of this paper is to introduce an exhaustive methodology to quantify the influence adverse environment conditions have in the mission fuel consumption and the associated emissions of nitrogen oxides (NOx). An emergency medical service (EMS) and a search and rescue (SAR) mission are used as case studies to simulate the effects of extreme temperatures, high altitude, and compressor degradation on a representative twin-engine medium (TEM) weight helicopter, the Sikorsky UH-60A Black Hawk. A simulation tool for helicopter mission performance analysis developed and validated at Cranfield University was employed. This software comprises different modules that enable the analysis of helicopter flight dynamics, powerplant performance, and exhaust emissions over a user-defined flight path profile. For the validation of the models implemented, extensive comparisons with experimental data are presented throughout for rotorcraft and engine performance as well as NOx emissions. Reductions as high as 12% and 40% in mission fuel and NOx emissions, respectively, were observed for the “high and cold” scenario simulated at the SAR role relative to the same mission trajectory under standard conditions.